2014
DOI: 10.1117/12.2043833
|View full text |Cite
|
Sign up to set email alerts
|

Volume estimation of multi-density nodules with thoracic CT

Abstract: The purpose of this work was to quantify the effect of surrounding density on the volumetric assessment of lung nodules in a phantom CT study. Eight synthetic multidensity nodules were manufactured by enclosing spherical cores in larger spheres of double the diameter and with a different uniform density. Different combinations of outer/inner diameters (20/10mm, 10/5mm) and densities (100HU/-630HU, 10HU/-630HU, -630HU/100HU, -630HU/-10HU) were created. The nodules were placed within an anthropomorphic phantom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…likely represent reasonable starting ranges for more complex nonuniform nodules. To test this, we initiated phantom studies of mixed-density nodules and our preliminary results were reported by Gavrielides et al 26 As mentioned but not emphasized earlier, we transformed the data for the purpose of stabilizing/equalizing the variance. This step is in fact critical for most of the analyses we performed.…”
Section: Discussionmentioning
confidence: 99%
“…likely represent reasonable starting ranges for more complex nonuniform nodules. To test this, we initiated phantom studies of mixed-density nodules and our preliminary results were reported by Gavrielides et al 26 As mentioned but not emphasized earlier, we transformed the data for the purpose of stabilizing/equalizing the variance. This step is in fact critical for most of the analyses we performed.…”
Section: Discussionmentioning
confidence: 99%
“…Phantom FDA Collection [Data Citation 5] contains CT images of the FDA anthropomorphic thorax phantom 18 configured with 8 nodule layouts scanned on a Philips Mx8000 IDT (Philips Healthcare, Andover, MA) and a Siemens Somatom Definition 64 scanner (Siemens Medical Solutions USA, Inc., Malvern, PA). Each nodule layout was scanned using 16 acquisition protocols that varied combinations of effective dose, pitch, and slice collimation, and were reconstructed with varying combinations of slice thicknesses and reconstruction kernels 19 . Ten exposures were acquired for each imaging protocol on each scanner.…”
Section: Data Recordsmentioning
confidence: 99%
“…7 To make maximal use of the spatially rich quantitative features in CT images, a considerable effort has been made to analyze the texture features. Some studies have shown that CT image acquisition can influence measurement of a single quantitative feature [8][9][10] or an ensemble of features. [11][12][13] Other phantom studies show that intrascanner and interscanner variabilities can depend on several factors including the phantom material composition, radiomic feature calculation method, and scan settings.…”
Section: Introductionmentioning
confidence: 99%